Little Witch Hazel : a year in the forest - Wahl, Phoebe (Tundra ; Tundra Books of Northern New York, an imprint of Penguin Random House Canada Young Readers, a division of Penguin Random House of Canada Limited, 2021)
"Little Witch Hazel is a tiny witch who lives in the forest, helping creatures big and small. She's a midwife, an intrepid explorer, a hard worker and a kind friend. In this four-season volume, Little Witch Hazel rescues an orphaned egg, goes sailing on a raft, solves the mystery of a haunted stump and makes house calls to fellow forest dwellers. But when Little Witch Hazel needs help herself, will she get it in time?"--